NATION LITERATURE AND NATIONAL INTEGRITY - Peng, Chew Fong (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2009)
Malay language is stipulated in the Law Article 152 as the national and official language of Malaysia. Therefore, literature using Malay language as the medium is adopted as the archipelago literature (Mohd. Taib Osman, 1971; Ismail Hussein, 1971). Considering that Malay language is understood by diverse ethnics, it can be concluded that the language holds an important role in developing understanding among people in Malaysia. The literature that grows and develops in the heart of a nation is the best foundation for building a united/integrated nation. Literary works have long contributed towards the culture and the civilization of a nation so that they become a part of the features and characteristics of a nation. Literary works are the encyclopedia of ideology, values, and cultures of all the people in Malaysia who give support towards the archipelago literature.